African Entrepreneurial Ecosystems: Form, Function & Structure Special Issue - Dawa, Samuel (Journal of Entrepreneurship and Innovation in Emerging Economies, 2022)
While opinion and evidence of the economic development and growth trajectory of most African countries is mixed and at times contradictory (Carmody et al., 2020; Cramer et al., 2020) , there is clear evidence that a large youthful population (Chigunta, 2017) and a strong desire for and interest in entrepreneurship, as evidenced by successive Global Entrepreneurship Monitor Reports will lead to the continued rise of startup businesses and entrepreneurial activity on the continent. Since the early conceptualisation of entrepreneurial ecosystems (Bahrami & Evans, 1995), building on the work of Moore (1993) who brought the ecological term into the social sciences, there is an understanding that ecosystems represent ‘a biotic community, encompassing its physical environment, and all the interactions possible in the complex of living and nonliving components’ (Acs et al., 2017, p. 1). Despite periods of theoretical interest in entrepreneurial ecosystems, the field does not boast a unifying definition or a robust theoretical framework. While ecosystem components have been identified and mapped—both regional and nationally in many African countries, there is a continued call for localisation of form, function and structure to accommodate the uniqueness of each context. This is even more relevant to the African continent, which is often seen a single homogenous market rather than a heterogeneous descriptor of 54 individual nations.
Keywords: African Entrepreneurial Ecosystems; Form; Function